Soil-dwelling arthropod assemblages in maize sprayed with entomopathogenic fungi from South Sumatra, Indonesia - SITI HERLINDA; MUHAMMAD YASKUR NASIR; SUWANDI SUWANDI; ERISE ANGGRAINI; CHANDRA IRSAN; JELLY MILINIA PUSPITA SARI; DELLANIA EKA RINDIANI (Society for Indonesian Biodiversity, 2025)
Abstract. Herlinda S, Nasir MY, Suwandi S, Anggraini E, Irsan C, Sari JMP, Rindiani DE. 2025. Soil-dwelling arthropod assemblages in maize sprayed with entomopathogenic fungi from South Sumatra, Indonesia. Biodiversitas 26: 3387-3396. This study examined effects of entomopathogenic fungi on abundance and species diversity of soil-dwelling arthropods associated with maize. The fungal species applied were Beauveria bassiana, Metarhizium anisopliae, and Penicillium citrinum. Pitfall traps and Berlese funnels were employed to collect arthropods soil-dwelling on the ground surface and within/below the soil, respectively. The identified arthropod guilds included predatory, herbivorous, and detritivore arthropods, with predatory arthropods being the most abundant. The arthropods were categorized into classes of Insecta, Collembola, Arachnida, and Diplopoda. The arthropods found from the ground surface and below the soil were 25 and 8 species, respectively. The total abundance (achieving 300 individuals/20 traps) of predatory arthropods did not differ significantly (P>0.05) across all treatments. The species diversity of below-ground predatory arthropods exhibited a significant decrease (P<0.05) after treatment with P. citrinum (H' from 0.71 to 0.39). The detritivore arthropod abundance from ground surface increased significantly (P<0.05) after being treated with B. bassiana (695 individuals/20 traps) compared to M. anisopliae (588 individuals/20 traps) and P. citrinum (569 individuals/20 traps) treatments. Therefore, M. anisopliae and P. citrinum could alter ground-surface arthropod assemblages. However, B. bassiana application may be integrated with soil-dwelling predatory arthropods for Integrated Pest Management (IPM) and for environmental safety.